Heart Rate Variability Parameters During Psychogenic Non-epileptic Seizures: Comparison Between Patients With Pure PNES and Comorbid Epilepsy - Romigi, Andrea; Ricciardo Rizzo, Giada; Izzi, Francesca; Guerrisi, Maria; Caccamo, Marco; Testa, Federica; Centonze, Diego; Mercuri, Nicola B.; Toschi, Nicola (Frontiers in Neurology, 2020)
Abstract INTRODUCTION Psychogenic nonepileptic seizures (PNES) may resemble epileptic seizures. Little is known about ictal ANS activity alterations induced by PNES in patients with pure PNES (pPNES) compared to PNES with comorbid epilepsy (PNES/ES). We aimed to compare heart rate variability (HRV) parameters and hence autonomic regulation in PNES in epileptic and non-epileptic patients. METHODS We obtained HRV data from video-electroencephalography recordings in 22 patients presenting PNES (11 pPNES and 11 PNES/ES) in awake, and supine states. We calculated HRV parameters in both time and frequency domains including low frequency (LF) power, high frequency power (HF), standard deviation of all consecutive R wave intervals (SDNN), and square root of the mean of the sum of the squares of differences between adjacent R wave intervals (RMSSD). We also evaluated approximate entropy (ApEn), cardiosympathetic index (CSI) and cardiovagal index (CVI). Four conditions were considered: basal condition (BAS), before PNES (PRE), during PNES (ICT) and after PNES (POST). RESULTS HRV analysis showed significantly higher ICT LF and LF/HF ratio versus each condition. We also found higher POST HF versus PRE and BAS, lower RRI in ICT versus each condition and PRE vs BAS. POST RMSSD was significantly higher compared to all other states. ICT CSI was significantly higher compared to all other states, whereas CSI was significantly lower in POST vs PRE and PRE CVI lower than ICT and higher in POST vs BAS and PRE. Also, ICT ApEn was lower than in all other states. Higher LF in PNES/ES versus pPNES was also evident when compared across groups. SIGNIFICANCE A few studies examined HRV alterations in PNES, reporting high sympathetic tone (although less evident than in epileptic seizures). Our data suggest a sympathetic overdrive before and during PNES followed by a post-PNES increase in vagal tone. A sympathovagal imbalance was more evident in pPNES as compared to PNES/ES.